Remarkably bright creatures : [large type] a novel - Van Pelt, Shelby (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
Staying busy has helped Tova cope ever since her son disappeared decades ago. So when her husband dies, she takes a job at the aquarium, where she meets Marcellus, an octopus that deduces what happened to her son.